A feasibility study of a psycho‐educational support intervention for men with prostate cancer on active surveillance. Issue 2 (9th December 2019) - Hughes, John G.; Leydon, Geraldine M.; Watts, Sam; Hughes, Stephanie; Brindle, Lucy A.; Arden‐Close, Emily; Bacon, Roger; Birch, Brian; Carballo, Lallita; Plant, Hilary; Moore, Caroline M.; Stuart, Beth; et al.
Abstract: Background: PROACTIVE is a psycho‐educational support intervention for prostate cancer patients managed on Active Surveillance. PROACTIVE is composed of two interdependent components: group workshops and internet‐delivered information modules. Aims: We conducted a feasibility study to determine the practicality of delivering PROACTIVE at two prostate cancer centres. Methods and Results: The feasibility study was a mixed‐methods randomized parallel‐group exploratory trial. Participants were randomised using a ratio of 3:1 PROACTIVE group to treatment as usual. Qualitative semi‐structured interviews and quantitative measures were completed at baseline, intervention completion (week 6), and at 6‐month follow‐up. Interview transcripts were analysed thematically using Framework analysis. Descriptive statistics were used to examine recruitment and retention rates and changing trends in outcome measures. Most aspects of the research design and PROACTIVE intervention were acceptable to those participating in the study. In particular, participants valued the opportunity to share and discuss experiences with other prostate cancer patients on Active Surveillance and receive detailed authoritative information. However, three issues were identified: (a) a low response rate (13 participants recruited, response rate 16%), (b) low utilisation of internet delivered information modules, (c) self‐perceived low levels of anxiety amongst participants with the majority perceiving their cancer as not impacting on their day‐to‐day life or causing anxiety. Conclusions: Due to these significant research design issues, it is not recommended PROACTIVE be evaluated in a large‐scale randomised controlled trial. Further research is required to explore the impact of Active Surveillance on anxiety amongst men with localized prostate cancer managed by Active Surveillance.